2013
DOI: 10.1002/2013jd020384
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term trends of biogenic sulfur aerosol and its relationship with sea surface temperature in Arctic Finland

Abstract: Forty‐seven years of week‐long total suspended particle samples from Kevo Finland were analyzed for methane sulfonic acid (MSA) and sulfate. Kevo is located 350 km north of the Arctic Circle. MSA and non‐sea‐salt sulfate (NSS‐SO4) showed clear seasonal trends. MSA peaks from May to July, coinciding with warmer waters and increased biogenic activity in the surrounding seas. NSS‐SO4 peaks in March with a minimum during the summer, the typical pattern for Arctic haze. MSA concentrations were found to be positivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 55 publications
5
28
0
Order By: Relevance
“…Sea ice may also have a significant impact on MSA distributions, and the MSA concentrations over the pack ice region in the central Arctic Ocean were generally lower than over the open waters at the ice edge in the Chukchi Sea. In addition, we found that higher MSA concentrations were associated with warmer sea surface temperature (SST), and a positive correlation between MSA and SST was observed, similar to the results reported by Laing et al (2013) [50]. with "−" and "+", respectively.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Sea ice may also have a significant impact on MSA distributions, and the MSA concentrations over the pack ice region in the central Arctic Ocean were generally lower than over the open waters at the ice edge in the Chukchi Sea. In addition, we found that higher MSA concentrations were associated with warmer sea surface temperature (SST), and a positive correlation between MSA and SST was observed, similar to the results reported by Laing et al (2013) [50]. with "−" and "+", respectively.…”
Section: Discussionsupporting
confidence: 87%
“…These results match those presented by Gabric et al, (2005) who simulated DMS production in response to global warming in the Arctic Ocean and found that increased SST and diminishing sea ice coverage could increase the DMS flux [11]. Laing et al, (2013) studied long-term MSA trends and found a positive relationship with SST in Arctic Finland (r 2 = 0.200, p < 0.001) [50]. Here, we have presented the MSA and SST data from the duration of the cruise.…”
Section: Sea Surface Temperaturesupporting
confidence: 83%
See 1 more Smart Citation
“…There have been no significant trends in either sulfate or BC at the observatory in Barrow, Alaska (Hirdman et al, 2010). Although measurements of methane sulfonic acid (MSA) from 1980 to 2009 show no net change in MSA at Alert (Sharma et al, 2012), MSA did increase from 2000 to 2009 associated with the northward migration of the marginal ice zone Sharma et al, 2012;Laing et al, 2013). Of the four northernmost observatories, the highest MSA concentrations are measured at Mount Zeppelin, likely due to its proximity to the waters between Greenland and northern Europe, that are a significant source of DMS from May to August (e.g., Lana et al, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…There have been no significant trends in either sulphate or BC at the observatory in Barrow, Alaska (Hirdman et al, 2010). Although measurements of methane sulphonic acid (MSA) from 1980 to 2009 show no net change in MSA at Alert (Sharma et al, 2012), MSA did increase from 2000 to 2009 associated with the northward migration of the marginal ice zone (Quinn et al, 2009;Sharma et al, 2012;Laing et al, 2013). Of the four northernmost observatories, the highest MSA concentrations are measured at Mount Zeppelin, likely due to its proximity to the waters between Greenland and Northern Europe, which are a significant 5 source of dimethyl sulphide (DMS) from May-August (e.g.…”
mentioning
confidence: 97%